Hearing loss in insulin-dependent diabetes mellitus - Celik, O.; Yalcin, S.; Celebi, H.; Ozturk, A. (Elsevier Ireland Ltd, 1996)
The purpose of this study was to examine the relationship between diabetes mellitus and hearing loss which is still controversial. Pure tone audiometry was performed in 75 patients with insulin-dependent diabetes mellitus, aged between 14 and 60 years (45 males and 30 females; average age 45.3 years), and in 40 randomly selected sex- and age-matched non-diabetic control subjects, using an Interacoustics Clinical Computer Audiometer Model AC5. The mean duration of diabetes in the study group was 15 ± 7 years. Complications such as retinopathy, nephropathy, and neuropathy had developed in 64% of the diabetics. Statistical analyses showed that the hearing of the diabetic patients was significantly worse than control subjects. Complications were found to have a significant effect on sensorineural hearing loss in diabetics. The influence of duration of diabetes was noticed on hearing threshold at mid and high frequencies, especially after the first decade of the disease.
Keywords: adolescent; adult; article; auditory threshold; controlled study; diabetic nephropathy; diabetic neuropathy; diabetic retinopathy; disease duration; female; human; insulin dependent diabetes mellitus; major clinical study; male; perception deafness; pure tone audiometry